One Fungus = One Name: DNA and fungal nomenclature twenty years after PCR - J.W. Taylor (IMA Fungus)
Some fungi with pleomorphic life-cycles still bear two names despite more than 20 years of molecular phylogenetics that have shown how to merge the two systems of classification, the asexual “Deuteromycota” and the sexual “Eumycota”. Mycologists have begun to flout nomenclatorial regulations and use just one name for one fungus. The International Code of Botanical Nomenclature (ICBN) must change to accommodate current practice or become irrelevant. The fundamental difference in the size of fungi and plants had a role in the origin of dual nomenclature and continues to hinder the development of an ICBN that fully accommodates microscopic fungi. A nomenclatorial crisis also looms due to environmental sequencing, which suggests that most fungi will have to be named without a physical specimen. Mycology may need to break from the ICBN and create a MycoCode to account for fungi known only from environmental nucleic acid sequence (i.e. ENAS fungi).